2020
DOI: 10.1101/2020.11.23.20235515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess Dietary Fructose Does Not Alter Gut Microbiota or Permeability in Humans: A Randomized Controlled Pilot Study

Abstract: Background and AimsNon-alcoholic fatty liver disease (NAFLD) is an increasing cause of chronic liver disease that accompanies obesity and the metabolic syndrome. Excess fructose consumption can initiate or exacerbate NAFLD due in part to a consequence of impaired hepatic fructose metabolism. Pre-clinical data have emphasized that fructose-induced altered gut microbiome, increased gut permeability, and endotoxemia play an important role in NAFLD, but human studies are sparse. The present study aimed to explore … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Diets supplemented with high-fructose corn syrup to induce NAFLD resulted in an increased Firmicutes:Bacteroidetes ratio 124,125 . However, a recent study of 10 obese patients found that fructose did not induce microbial changes 126 . Since this study used a solid form of fructose, it is possible that the small intestine efficiently prevented fructose spillover to the colon.…”
Section: Role Of the Gut Microbiota In Nafldmentioning
confidence: 94%
See 1 more Smart Citation
“…Diets supplemented with high-fructose corn syrup to induce NAFLD resulted in an increased Firmicutes:Bacteroidetes ratio 124,125 . However, a recent study of 10 obese patients found that fructose did not induce microbial changes 126 . Since this study used a solid form of fructose, it is possible that the small intestine efficiently prevented fructose spillover to the colon.…”
Section: Role Of the Gut Microbiota In Nafldmentioning
confidence: 94%
“…However, the human relevance of fructose-induced gut leakiness and microbial dysbiosis is still controversial. A recent clinical study showed that obese participants given a daily dose of 75 g of fructose over a course of a few weeks displayed no gut permeability or endotoxemia 126 . It is possible that the concentration of fructose administered in animal studies is beyond the concentrations received by typical human consumption, causing chronic and systemic changes.…”
Section: Effect Of Fructose On Colon Integritymentioning
confidence: 99%
“…Indeed, SCFAs have already been shown to protect against the progression of gut dysbiosis and hypertension. 71 However, it is important to note that median dietary fructose (74 g day −1 ) does not alter gut microbiota or permeability in humans, 72 which may be associated with the unchanged BP. [28][29][30][31][32] Fig.…”
Section: Gut Dysbiosis Contributes To Hf-induced Ssh Via the Activati...mentioning
confidence: 99%